Evaluasi perhitungan dan pelaporan Pajak Pertambahan Nilai pada agen LPG 3 kg PT Chas Gas Adhikarya di Manado - Buabangga, Purigintalita; Sabijono, Harijanto; Tangkuman, Steven Josia (Yayasan Widyantara Nawasena Raharja, 2025)
The imposition of Value Added Tax (VAT) on 3 kg LPG agents applies to the revenue generated from the sale of 3 kg LPG gas cylinders. This revenue is calculated based on the rates and procedures outlined in Minister of Finance Regulation No. 62 of 2022 concerning VAT on the delivery of certain liquefied petroleum gas (LPG). This study aims to analyze and evaluate the calculation and reporting of VAT by the 3 kg LPG agent, PT Chas Gas Adhikarya, in Manado. The research employs a descriptive method with a qualitative approach. The findings indicate that PT Chas Gas Adhikarya has calculated VAT in accordance with the applicable regulations. However, the company still experiences delays in VAT payment and reporting.